Effect of different size of rotor bars on induction motor efficiency - Pungut, Ibrahim; Ismail, Daut, Prof. dr.; Rosnazri, Ali; Yanawati, Yahya; Nor Shafiqin, Shariffuddin; Mastika, Abdullah (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.